Effects of Different Previous Crops and Nitrogen Rates on Double Cropping Maize (Zea mays L.) - GUL, ISMAIL; AKINCI, CUMA; DORAN, ILHAN; KILIC, HASAN; BAYTEKIN, HARUN (Asian Journal of Chemistry, 2010)
The effects of previous crops (wheat, barley, lentil, Hungarian vetch and fallow) and different nitrogen rate (0, 120, 160, 200 and 240 kg N ha-1) on grain yield and yield components of maize (Zea mays L.) were evaluated under irrigated conditions in Diyarbakir, Turkey in the 1999-2000, 2000-2001 growing seasons. Maize was grown in summers and wheat, barley, lentil and Hungarian vetch in winters. In the study, grain yield of maize varied between 6340.3 and 11598.9 kg ha-1. It was determined that Hungarian vetch was suitable for previous crop and 160 kg ha-1 N rate is the best nitrogen rate in maize production. According to the interaction of previous crop-nitrogen rate, the highest yield was obtained from the subject grown after lentil and Hungarian vetch with 160 kg N ha-1. Maize following legumes in rotation did not respond to applications over 160 kg N ha-1, while barleymaize, wheat-maize increased at all levels of N applied. Fallowsorghum did not respond to application over 200 kg N ha-1.